2016
DOI: 10.1002/chem.201604793
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)‐Catalyzed Enantioselective [3+2]‐Cycloaddition Reaction of α‐Silylimines: A Facile Route to Quaternary‐Carbon‐Rich Scaffolds

Abstract: A silver-catalyzed highly enantioselective 1,3-dipolar cycloaddition reaction of α-silylimines with pyrone-based trisubstituted olefins was developed affording bi- and tricyclic α-quaternary-carbon-rich pyrano-pyrrolidines in excellent yields. The tricyclic benzopyrone adducts thus obtained were efficiently transformed into highly complex tetracyclic scaffolds supporting four consecutive stereogenic centers with three quaternary carbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Interestingly, reactions of 7 derived dipole performed better with aryl or alkyl ketimine 1 than with aldimine ( 1 , R 1 =H) or iminoester ( 1 , R 1 =CO 2 Et, Scheme ). Notably, α‐silyl imines ( 9 ) have rarely been explored in cycloaddition chemistry and are interesting substrates for generating small molecules embodying quaternary centers and complex stereochemical frameworks . Another reaction screening revealed that catalytic AgOAc and phosphine complex in acetonitrile could transform 1‐CO 2 Et with 9 into syn ‐imidazolidine 10 (d.r.=87:13) as major adduct that bear two consecutive quaternary stereocenters (Table S1 in Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, reactions of 7 derived dipole performed better with aryl or alkyl ketimine 1 than with aldimine ( 1 , R 1 =H) or iminoester ( 1 , R 1 =CO 2 Et, Scheme ). Notably, α‐silyl imines ( 9 ) have rarely been explored in cycloaddition chemistry and are interesting substrates for generating small molecules embodying quaternary centers and complex stereochemical frameworks . Another reaction screening revealed that catalytic AgOAc and phosphine complex in acetonitrile could transform 1‐CO 2 Et with 9 into syn ‐imidazolidine 10 (d.r.=87:13) as major adduct that bear two consecutive quaternary stereocenters (Table S1 in Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…For example, compound 1' exhibits significant inhibition against 5-lipoxygenase in the cell-free assay, and spiropyrrolidines 2' – 6' were found to be cytotoxic against K562 cells, while fluorochromenopyrrolidines 7' –8' can be used for treating erectile disorders (Scheme a) . The existing approaches toward chromenopyrrolidines routinely rely on the [3 + 2] cycloaddition of chromones or their derivatives with in situ -generated azomethine ylides (Scheme b) via heating, acid, transition-metal, or Lewis base catalysis in which highly active carbonyl compounds, such as formaldehyde or α-activated ketones, were required. On the other hand, even though chromones were extensively utilized as reactants in many cases of photocatalysis, they were merely used as Giese-type addition acceptors to deliver 2-functionalized chroman-4-ones as the final products, while photocatalyzed annulation of chromones was rarely disclosed .…”
mentioning
confidence: 99%
“…Alkenes bearing two electron-withdrawing groups have been widely used as electrophiles in a variety of transformations including catalytic asymmetric reactions such as cycloadditions, Michael reactions, and Friedel–Crafts reactions due to their electron-deficient properties. Owing to their greater reactivity, alkenes bearing two electron-withdrawing groups have been employed as key intermediates in natural product synthesis .…”
mentioning
confidence: 99%